Three New Records of Gammarid Amphipod in Songkhla Lake, Thailand - Kotchakorn Rattanama; Manasawan Saengsakda Pattaratumrong; Prawit Towatana; Koraon Wongkamhaeng (Tropical Life Sciences Research, 2016)
Songkhla Lake is known as the most popular area for gammarid amphipod studies in the Gulf of Thailand. The first gammarid amphipod study was investigated in 1925 by Chilton. After that, there are various studies including diversity, ecology, and biology. In this study, gammarid amphipod in Songkhla Lake were collected from year 2010 to 2014. In this study, three newly recorded amphipods had been reported namely Hyale dollfusi Chevreux, 1911, Grandidierella megnae (Giles, 1888), and Hourstonius japonica (Hirayama, 1983) which had not been previously reported from the Thai waters. The gammarid amphipods had been catalogued. Their characteristics had been described and illustrated. All specimens were deposited at Princess Maha Chakri Sirindhorn Natural History Museum, Prince of Songkla University, Thailand.